1999
DOI: 10.1677/erc.0.0060131
|View full text |Cite
|
Sign up to set email alerts
|

Local estrogen biosynthesis in males and females.

Abstract: It is now apparent that in men and in postmenopausal women, estrogens have important physiological and pathophysiological roles. However, importantly, these actions are at a ocal level, namely paracrine, autocrine, and even 'intracrine' rather than endocrine in the classical sense. Thus for example local estrogen biosynthesis in the bones of men plays a hitherto unsuspected role in the maintenance of bone mineralization and in epiphyseal fusion; and in the testes, estrogen is essential for male germ cell devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 42 publications
(27 reference statements)
5
107
0
7
Order By: Relevance
“…(17) A second protective mechanism is that the greater amount of adipose tissue available enhances the ability to produce endogenous estrogens, which preserve BMD. (18) Third, women who carry more fat mass may benefit from cushioning of their hip by gluteofemoral adipose tissue, which reduces impact forces when they fall and hence their chance of fracture. (19) A protective association of physical activity, often measured as leisure time activity in older studies, with hip fracture has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17) A second protective mechanism is that the greater amount of adipose tissue available enhances the ability to produce endogenous estrogens, which preserve BMD. (18) Third, women who carry more fat mass may benefit from cushioning of their hip by gluteofemoral adipose tissue, which reduces impact forces when they fall and hence their chance of fracture. (19) A protective association of physical activity, often measured as leisure time activity in older studies, with hip fracture has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…(16) This protective effect has been attributed to higher levels of BMD resulting from increased chronic strain on the bones, an increased production of estrogens from larger stores of adipose tissue, and/or a reduced impact from falls because of a greater cushioning by subcutaneous adipose tissue. (17)(18)(19) Since body mass index (BMI) may be part of the causal pathway for the effect of physical activity on hip fracture risk, and because active people tend to have a lower body weight than inactive people, (9,20) the independent effects of BMI and physical activity on hip fracture risk need clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Although estrogen has a well-established effect on the skeleton [23], our findings showed greater bone mass and lower bone turnover in HRT(+) compared with HRT(−) subjects for the normal-weight group, but not the obese group. This indicates that women of lower body weights may be more responsive to HRT compared with obese subjects, whose higher body fat content may be a significant endogenous source of estrogen [24], and whose higher weight-bearing (compared with normal-weight women) is expected to independently promote higher bone mass. Nevertheless, once women with higher endogenous sources of estrogen (i.e., as in obesity) take HRT, these endogenous sources are less likely to be important.…”
Section: Discussionmentioning
confidence: 99%
“…A greater body weight may prevent the decrease in E 2 due to local synthesis of estrogen in adipose tissue (28) and may protect against bone loss. In addition, the decreases in E 2 during weight reduction tended to be associ-ated with decreases in calcium absorption in lean rats.…”
Section: Discussionmentioning
confidence: 99%